The importance of social network relationships during the socialisation process of new employees - Paul, Divya Rebecca (My University, 2011)
Organisation socialisation is the process by which an individual acquires the attitudes, behaviour, and knowledge she or he needs to participate as an organisation member (Van Maanen & Schein, 1979). During socialisation, organisations seek to mould new employees to fit its needs and employees attempt to define acceptable work roles for themselves within the organisation (Fisher, 1986). Several scholars believe that an important way in which socialisation occurs is through social interactions between newcomers and „insiders‟ or more experienced members of their organisation (Feldman, 1981; Louis, 1990; Reichers, 1987). Relationships might be important, but little is known about the types of relationship patterns that are most conducive to effective socialisation (Morrison, 2002). This research will view the socialisation process from the perspective of social network structure and examine the effect of the relationships on socialisation outcomes.
Keywords: Socialisation outcomes; Social network analysis; Newcomer learning and assimilation